Strategi Pemulihan Pariwisata Pasca Penanganan Pandemi Covid-19 di Provinsi Bali - Desak Ayu Putu Suciati; I Made Suadnya (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2021)
The island of Bali is one of the main destinations in Indonesia which has long been known to foreign countries. The number of tourist visits to Bali each year has increased, in 2017 which means 5,697,739 tourists experienced an increase of 6.54% in 2018 to 6,070,473 tourists. The condition of tourists in Bali has experienced a rapid decline in 2020. This is due to a deadly flu outbreak that has paralyzed the joints of the world economy. This outbreak is known as SARS - CoV - 2 (Covid - 19), which initially appeared locally in Wuhan City, Hubei Province, China (People's Republic of China) in December 2019. The Bali government said there were 337 positive cases of Covid-19 in the whole region. This number ranks tenth among other provinces. The decline in the Bali tourism industry has also had an impact on tourism workers. At least 1.1 million people work in the company's MSME department. Tourism is one of the sectors hardest hit by the pandemic. The tourism structure that must be implemented, the tourism concept, destination development, and tourist attraction strategies. To attract tourists again, there are several strategies that will be implemented. According to (Paramita, IBG and IGGP Arsa Putra, 2020) there are 7 strategies that must be implemented so that tourists coming to Bali feel safe and comfortable despite this pandemic. These strategies are, High Standard Sanitation, High Standard Security, Staycation, Niche tourism, Solo travel tours, Wellness tours, Virtual tourism.Keywords: Tourism, Covid-19, Attraction Strategy